2021
DOI: 10.1007/s00204-021-03140-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of co-formulants on the absorption and secretion of active substances in plant protection products in vitro

Abstract: Currently, the authorisation process for plant protection products (PPPs) relies on the testing of acute and topological toxicity only. Contrastingly, the evaluation of active substances includes a more comprehensive set of toxicity studies. Nevertheless, mixture effects of active ingredients and co-formulants may result in increased toxicity. Therefore, we investigated effects of surface active co-formulants on the toxicity of two PPPs focussing on qualitative and quantitative toxicokinetic effects on absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…10,23 Toxicity of co-formulants The increasing use of PPPs has led to widespread concerns about their adverse effect on the environment and especially on human health, particularly those surfactants with non-ionic properties. 7 According to the harmonized classification and labeling approved by the European Union, 1,2-benzisothiazol-3(2H)-one is very toxic to aquatic life and harmful if swallowed. Moreover, this compound causes serious eye damage, skin irritation and might even cause an allergic skin reaction.…”
Section: Study Of Type Of Formulationsmentioning
confidence: 99%
See 3 more Smart Citations
“…10,23 Toxicity of co-formulants The increasing use of PPPs has led to widespread concerns about their adverse effect on the environment and especially on human health, particularly those surfactants with non-ionic properties. 7 According to the harmonized classification and labeling approved by the European Union, 1,2-benzisothiazol-3(2H)-one is very toxic to aquatic life and harmful if swallowed. Moreover, this compound causes serious eye damage, skin irritation and might even cause an allergic skin reaction.…”
Section: Study Of Type Of Formulationsmentioning
confidence: 99%
“…12 However, no further toxicological evaluation or authorization is required for co-formulants, because they are commonly subject to the REACH (Registration, Evaluation, Authorization and restriction of Chemicals) regulation and hence toxicologically tested and assessed depending on their annual production volume. 7 Nevertheless, some studies have demonstrated that some co-formulants, which might not be toxic themselves, can influence the toxicity of PPPs via toxicodynamic and toxicokinetic interactions. 8 Consequently, the Commission Regulation (EU) 2021/383 sets a list of co-formulants that are not accepted for inclusion in PPPs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Additionally, other authors have pointed at synergistic effects between the active substances and coformulants, which could result in increased toxicity. 5,6 Concerning EU Regulations, Regulation EC No 2021/383 lists the forbidden co-formulants for use in PPPs or marketed adjuvants. 7 However, this regulation generally allows concentrations less than 0.1% (w/w) of these unacceptable coformulants unless otherwise noted, as these could be unintentional impurities.…”
Section: ■ Introductionmentioning
confidence: 99%